Effects of working conditions on healthcare providers’ provision of quality maternal healthcare services at Kamuzu Central hospital and Bwaila district hospital in Lilongwe district, Malawi - Mawanga, Jacqueline Zambezi (2021)
In developing countries, health workforce is one of the predominant challenges affecting the health care systems’ function of providing quality services including maternal care. The challenge relates to how these countries establish conducive working conditions that attract and retain health workers into the health care sector and enable them to perform effectively and efficiently to improve maternal healthcare services in hospitals. The research study was assessing the effects of working conditions on healthcare provider’s ability to provide quality maternal healthcare services in two major hospitals; Kamuzu Central hospital and Bwaila district hospital of Lilongwe district. Methods: The research study was a qualitative descriptive approach applying in-depth interviews and focus group discussions using interview and discussion guides respectively. Participants were selected using purposive sampling. Data was digitally collected using audio recorders. The data was manually analyzed using thematic analysis. The study has reviewed many working conditions that surround health workers at maternity departments of these two major public hospitals in Lilongwe district. The status of these identified working conditions received mixed reactions as majority of study participants expressed them as poor and pathetic, and that hugely affects their ability to provide quality maternal healthcare services. Health system and health managers have major role to play in supporting health workers available on the ground in order to improve maternal healthcare services that have higher potential to reduce maternal mortality rates in this country.Both health workers and managers explained their perceptions on existing working conditions and how they are related to work motivation and overall performance.